Kinerja Protokol Contact-Based Routing (CBR) dengan menggunakan Management Buffer Shortest Life First (SHLI) pada Delay Tolerant Network - Roy Marten Sirait; Primantara Hari Trisnawan; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Delay Tolerant Network (DTN) is a network protocol that can connect contacts between devices with unstable connectivity with high delay times. DTN network protocol applies the store-carry-and-forward concept to send messages so that it does not always have an end-to-end connection. The multi-copy message-copying scheme is an effective for message routing approach between the source and destination nodes. However, this scheme results in a large number of unwanted messages being copied, resulting in a high number of remaining packets in the network. To solve this issue, a message copying process policy can be created. Contact-based routing (CBR) is a protocol that can observe the mobility property of each connected node by looking at the amount of node encounters in the past. The message copying selection policy on the CBR, can reduce the average delivery delay time, reduce the remaining packets on the network, but still be able to maintain the success rate of message delivery when compared to the routing protocols used in general. The addition of a management buffer is also needed to control the storage space owned by each node. The simulation results show an increase in the value of delivery probability up to 51.5%, a decrease in the value of overhead ratio up to 24.9%, and average latency up to 20.1% when compared to the flooding-based routing protocol that is often used.